MULTIPLEX PCR FOR DETECTION OF CAPSULAR POLYSACCHARIDES TYPES OF Streptococcus pneumoniae CLINICAL ISOLATES IN BALI - Fatmawati, Ni Nengah Dwi; Tarini, Ni Made Adi; Mayura, I Putu Bayu (International Journal of Biosciences and Biotechnology; Vol 2 No 2 (2015))
Streptococcus pneumoniae is causative agent of non-invasive and Invasive Pneumococcal Diseases(IPD). One of the major virulence factors is capsular polysaccharides (CPS). The CPS is known as thepneumococcal vaccine component. Several types of S. pneumoniae CPS are dominant in Indonesiasuch as types 6, 23, 15, 33 and 12 in West Nusa Tenggara, type 7F in Jakarta, and types 6A/B dan15B/C in Central Java. No data is reported from Bali related to S.pneumoniae CPS typing. Therefore,the aim of this study was to determine CPS types of S. pneumoniae isolates in Clinical MicrobiologyLaboratory, Sanglah General Hospital, Denpasar, Bali by using Multiplex PCR. Twenty-one isolatesthat were isolated from blood (11/52.4%), sputum (5/23.8%), and other clinical specimens (5/23.8%)were included in this study. Identification of S. pneumoniae was based on optochin test and presenceof pneumolysin gene (ply). Uniplex PCR was conducted to determine capsular type of each isolates,and then continued with Multiplex PCR 1 and 2, which used in-house positive controls. All isolateswere positive for the presence of ply, confirming the isolates were S. pneumoniae. Moreover, thisstudy showed that type 19F was the predominant type (7 isolates (66.7%)); 2 isolates (9.5%) werepositive for each type 23F and also for type 6A/B; and, there was only 1 isolate (4.8%) for each type7F and 15B/C. Total of 8 isolates (38.1%) were found to be nontypeable isolates. Multiplex PCR wassuccessfully identified different types of CPS. Development of Multiplex PCR could help indiagnosing and identifying capsular type of S. pneumoniae simultaneously.
Keywords: Streptococcus pneumoniae, Capsular Polysaccharides (CPS), Multiplex PCR, Positive Control, Pneumococcal vaccine